MATHEMATICAL MODELLING OF THIN-LAYER DRYING OF KIWIFRUIT SLICES - Doymaz, Ibrahim (WILEY, 2009)
The effect of temperature on the drying kinetics of kiwifruit was investigated. The drying process was carried out at temperatures of 50, 55 and 60C, air velocity of 2.4 m/s and relative humidity between 10-25%. Drying time decreased considerably with increased air temperature. Drying process took place in the falling rate period. Twelve mathematical models available in the literature were fitted to the experimental data. The models were compared by four statistical parameters; i.e., determination of coefficient, mean relative percent error, reduced chi-square and root mean square error, and the best-fit model was selected. The modified Henderson and Pabis and Verma et al. models were given the best results in describing thin-layer drying of kiwifruits. The effective diffusivity of water during air-drying varied from 1.743 to 2.241 x 10(-10) m(2)/s over the temperature range investigated, with activation energy equal to 22.48 kJ/mol.
Keywords: HOT-AIR; REHYDRATION CHARACTERISTICS; MOISTURE DIFFUSIVITY; OSMOTIC DEHYDRATION; KINETICS; MICROWAVE; PRETREATMENTS; SELECTION; GREEN; PLUM; Food Science & Technology